Biofield therapies: Guidelines for reporting clinical trials - Richard Hammerschlag; Meredith L. Sprengel; Ann L. Baldwin (Elsevier, 2024)
A set of guidelines has been developed to help improve reporting of clinical trials of biofield therapies. The need for enhanced transparency when reporting trials of this family of integrative health practices, e.g., External Qigong, Healing Touch, Reiki and Therapeutic Touch, has been advocated in systematic reviews of these studies. The guidelines, called Biofield Therapies: Reporting Evidence Guidelines (BiFi REGs), supplement CONSORT 2010 by including details of the intervention protocols relevant to biofield therapy trials. BiFi REGs evolved through a draft document created by a core group, two rounds of a Delphi process with an international group of subject matter experts and two panels, meeting via Zoom, which included editors of complementary and integrative medicine journals. BiFi REGs comprises a 15-item Intervention checklist. Modifications of two other CONSORT topic areas are also proposed to enhance their relevance to trials of biofield therapies. Included for each item are an explanation, and exemplars of reporting from peer-reviewed published reports of biofield therapy trials. When used in conjunction with all other items from CONSORT 2010, we anticipate that BiFi REGs will expedite the peer review process for biofield therapy trials, facilitate attempts at trial replication and help to inform decision-making in the clinical practice of biofield therapies.